Towards a Better Understanding of the Antecedents of IJVs’ Knowledge Acquisition and its Outcome: A Two-Fold Proposed Framework - Elhachemi, Tamma; Jaguli, Abd Rahim; Ahmad, Fakhrorazi (UUM Press, 2019)
In the era of globalization and technological advancement, developing and transition economies focus in seeking to attract FDI as means of obtaining capital and new technology. This in turn will open the door for local firms to enter into international joint ventures (IJVs) to acquire necessary capabilities by gaining access to foreign MNCs’ resources, knowledge, and skills. While foreign partners have agreed to pool their capital, knowledge, and technology, however, there is no guarantee of successful ventures. Drawing upon the intensive literature on knowledge transfer and strategic alliances, this paper aims to present potential antecedents and consequences of IJVs’ knowledge acquisition through proposing a two-fold conceptual framework to be tested empirically in future studies. The proposed framework suggests transfer mechanisms, management practices and formal mechanisms that link to IJVs’ knowledge acquisition. These will in turn lead to IJVs’ competitiveness. To support and justify the suggested framework, methodology and literature reviews are presented.